Effect of Giving Young Papaya (Carica Papaya L.) Fruit Extract on Endometrial Histology of Female Rats (Rattus Norvegicus) - Cecen Suci Hakameri; Tofrizal; Elly Usman (Science Midwifery, 2020)
Young papaya contains several phytochemicals such as saponins, alkaloids and flavonoids. The active compounds in young papaya are thought to be able to cause disruption of the hypothalamic-pituitary pathway which causes disruption of GnRH secretion and affects the ovarian cycle which affects the normal endometrial cycle. The aim of this study was to determine the effect of giving young papaya fruit extract (Carica papaya L.) on endometrial histology of female rats (Rattus norvegicus). This study uses the Post Test Only Control Group method. Total samples were 24 rats (Rattus norvegicus), 2-3 months old and 200-300 grams in weight. Samples were taken randomly, divided into 4 groups. Group (K) without being given treatment. Group (P1) was given 200 mg / 200gr BW of young papaya extract. Group (P2) was given young papaya fruit extract 400 mg / 200gr BW. Group (P3) was given young papaya fruit extract 600 mg / 200gr BW. After 20 days of treatment, the endometrial thickness and density of the endometrium were measured. The results showed that the administration of young papaya fruit extract (Carica papaya L.) caused changes in the thickness of the endometrium and inhibited endometrial gland density. The results of statistical analysis using the one way ANOVA test showed the effect of giving papaya extract on endometrial thickness (p = 0.009) and the effect of giving papaya extract on gland density. It can be concluded that there is an effect of giving young papaya (Carica papaya L.) fruit extract on endometrial thickness and endometrial gland density.